2021
DOI: 10.35371/aoem.2021.33.e4
|View full text |Cite
|
Sign up to set email alerts
|

Association of phthalates and early menarche in Korean adolescent girls from Korean National Environmental Health Survey (KoNEHS) 2015–2017

Abstract: Background Phthalates are one of renowned endocrine-disrupting chemicals, although inconsistent results are present around their effect on onset of menarche. Our hypothesis is that pre-pubertal exposure to phthalates is associated with acceleration of menarche. Methods We analyzed a total of 236 middle school (7th to 9th grade) girls from Korean National Environmental Health Survey 2015 – 2017. We used multiple linear regression to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
2
4
1
Order By: Relevance
“…This study detected that the mean level of monobutyl phthalates was higher in PP group than the control group and showed a significant difference. This was compatible with the third round of KoNEHS that was conducted by Park et al [33] to describe the Korean population and assess exposure levels to different chemicals in which they found that the possibility of early menarche was significantly increased in a high concentration of MnBP compared to low concentration. Furthermore, Zhang et al [43] found that phthalate metabolites levels (MMP, MnBP, mono(2-ethyl-hexyl) , and MEP) were related to increased breast development stage, rapid breast progression, and earlier menarche.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study detected that the mean level of monobutyl phthalates was higher in PP group than the control group and showed a significant difference. This was compatible with the third round of KoNEHS that was conducted by Park et al [33] to describe the Korean population and assess exposure levels to different chemicals in which they found that the possibility of early menarche was significantly increased in a high concentration of MnBP compared to low concentration. Furthermore, Zhang et al [43] found that phthalate metabolites levels (MMP, MnBP, mono(2-ethyl-hexyl) , and MEP) were related to increased breast development stage, rapid breast progression, and earlier menarche.…”
Section: Discussionsupporting
confidence: 85%
“…This agreed with Srilanchakon et al [31] who found significant difference between idiopathic precocious puberty, early puberty, and control regarding BMI and Hashemipour et al [32] who found significant difference between central precocious puberty group and control. It was contrary to Park et al [33] who reported that there was no significant difference between the early menarche group and the normal menarche. Also, Buluş et al [5] reported that there was no statistical difference between the CPP group, PPP group, and control regarding BMI.…”
Section: Discussioncontrasting
confidence: 79%
“…Modeling menarche [45,73,74] or early onset of menarche [75] as a binary outcome, four previous studies reported increased odds of (early) menarche in relation to phthalate exposure, which is consistent with our findings. In an 18-month follow-up study of 208 girls (6 to 13 years) from Shanghai, 5OH-MEHP and 5oxo-MEHP were associated with a 70% increase in the odds of having reached menarche [45].…”
Section: Epidemiological Evidence For Phthalatessupporting
confidence: 92%
“… 38 Since phthalates are used in almost all modern industries, studies to determine their health effects on humans have been widely performed. Phthalates are well known for their endocrine-disrupting mechanisms, including suppression of the reproductive tract, childhood obesity, early menarche, 38 39 and other adverse effects in various organs are actively revealed. MEOHP is a metabolite of di-2-ethylhexyl phthalate (DEHP).…”
Section: Discussionmentioning
confidence: 99%